The burden of AIDS: a time series analysis of thirty-five years of the epidemic in Brazil. Issue 11 (2nd November 2018) - Traebert, Jefferson; Traebert, Eliane; Schuelter-Trevisol, Fabiana; Cortez Escalante, Juan Jose; Schneider, Ione Jayce Ceola
ABSTRACT: Although traditional epidemiological information, such as mortality rate and prevalence or incidence rates, is relevant to the understanding of AIDS epidemiology in Brazil, a more complete indicator would be recommended. The aim of this study was to estimate the burden of AIDS and its trends in Brazil from 1980 to 2015. An ecological study using secondary data on mortality, morbidity and demography was carried out. Data were collected from official health information sources. Disability-adjusted life years (DALY) index was estimated by year. Trend analysis of the rates were performed using a segmented linear regression method. There were 826, 452 confirmed HIV/AIDS cases and 302, 614 deaths from AIDS-related causes in the studied period. The greatest burden occurred between 1994 and 1996, with a significant increase in the burden of AIDS for both sexes. The burden of AIDS in Brazil remains high, with a tendency to increase significantly the DALY rates in the study period. However, trend reversals in the DALY rates and in the mortality component, with a consequent increase in the morbidity component, were identified from 1995 onwards.